The extractive sector bureaucracy: An analysis of the high bureaucracy professional profile of the Ministerio de Energía y Minas during the context of the commodity boom (2006-2016). - Arriola, Addier (2017)
This article focuses in the analysis of the high bureaucracy professional profile (ministers, vice ministers and directors) from the Ministerio de Energía y Minas (MINEM) during the context of the so-called commodity boom (2006 – 2016), a period characterized by the sustai- ned rise in the price of raw materials. In order to achieve this objective, we have elaborated a monitoring database picking up demographic characteristics; educational trajectories and career paths; career stability; employment links; and political party ties from 73 top managers of the MINEM organic units that worked in the period from 2006 to 2016. Thus, this research has as objectives to provide a descriptive professional profile of the high bureaucracy of the MINEM during the so-called boom of raw materials and to analyze and discuss their professionalization from a theoretical framework that relates bureaucratic quality to state capacity.